2012
DOI: 10.1109/tvcg.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of MagnetViz—A Graph Visualization Tool

Abstract: MagnetViz was designed for the interactive manipulation of force-directed graph layouts, allowing the user to obtain visualizations based on the graph topology and/or the attributes of its nodes and edges. The user can introduce virtual magnets anywhere in the graph and these can be set to attract nodes and edges that fulfill user-defined criteria. When a magnet is placed, the force-directed nature of the layout forces it to reorganize itself in order to reflect the changes in the balance of forces, consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…McGuffin and Jurisica's approach lets users modify a node‐link diagram by applying a chosen layout algorithm on a selected subset of nodes [MJ09]. In contrast, MagnetViz [SF12] allows users to reorganize the entire diagram through virtual magnets that attract nodes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…McGuffin and Jurisica's approach lets users modify a node‐link diagram by applying a chosen layout algorithm on a selected subset of nodes [MJ09]. In contrast, MagnetViz [SF12] allows users to reorganize the entire diagram through virtual magnets that attract nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Magnets are based on the MagnetViz concept [SF12]; they apply an attraction force on a selection of nodes, which reshapes the layout (Fig. b).…”
Section: Graphcoiffurementioning
confidence: 99%
“…The group has started to work with social networks as an experimental area for graph visualization techniques. A technique (and tool) named MagnetViz [3] was designed for the interactive manipulation of force-directed graph layouts, allowing users to obtain visualizations based on the graph topology and/or the attributes of its nodes and edges. Users can introduce virtual magnets anywhere in the layout and these can be set to attract nodes and edges that fulfill user-defined criteria.…”
Section: Interactive Visualization Of Social Networkmentioning
confidence: 99%
“…The original nested model focuses on providing guidance in terms of choosing appropriate validation techniques at each level and stresses the negative and cascading implications of poor design decisions. It has provided guidance, motivation, framing, and ammunition for a broad range of visualization papers, including problem-driven design studies, [20][21][22][23][24][25] technique-driven work, 26 evaluation, 27,28 models, 3,[29][30][31][32][33][34] and systems. 35,36 While we and others have used the nested model extensively as a way to guide decisions about evaluation and design, we have found that it falls short in capturing and describing design decisions at the level of detail needed for thorough analysis.…”
Section: Introductionmentioning
confidence: 99%